1994
DOI: 10.1111/j.1440-1746.1994.tb01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of pancreatic stones by oral trimethadione in patients with chronic calcific pancreatitis

Abstract: The effect of oral dissolution therapy for pancreatic stones was evaluated in patients with chronic calcific pancreatitis. The anti-epileptic agent trimethadione was given orally to 30 outpatients at a dose of 0.9-1.5 g daily. On plain X-ray films and CT scans of the abdomen, pancreatic stones began to be dissolved around 8 months of treatment, and diminished in size and number or disappeared in 21 patients (70%) during the mean follow-up period of 32 months. The effect of trimethadione treatment on dissolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…In agreement, litholysis was only achieved in patients with good adherence. In the present and previous studies [17], there was no case in which litholytic therapy had to be discontinued because of adverse effects of trimethadione. The concomitant mechanisms of action of multiple procedures should also be considered in terms of treatment success.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In agreement, litholysis was only achieved in patients with good adherence. In the present and previous studies [17], there was no case in which litholytic therapy had to be discontinued because of adverse effects of trimethadione. The concomitant mechanisms of action of multiple procedures should also be considered in terms of treatment success.…”
Section: Discussionmentioning
confidence: 80%
“…Two-thirds of the patients had alcoholrelated chronic pancreatitis, and the remaining patients had idiopathic pancreatitis. Plain X-ray film and/or computed tomography (CT) scans of the upper abdomen showed that the distribution of the stones was diffuse in 80%, and the size of the stones [17] was small and mixed (large and small) in 94%.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations